2011
DOI: 10.1007/s12564-011-9162-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of college experiences on male and female student leadership capacity in Taiwan

Abstract: This study examined how college experiences affect student leadership capacity in the general college population, as well as in male versus female populations. The data were drawn from a longitudinal sample of students across 156 colleges in Taiwan. Results of this study indicated that student leadership capacity increased after college entry. After controlling for pre-college experiences and structural characteristics, various college experiences of curricular learning, cocurricular learning, and interpersona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
1
4
0
2
Order By: Relevance
“…No matter which of the two explanations holds more truth, the result of this study indicates that in the near future, Chinese females may very likely rise to assume a substantial portion of leadership roles in Chinese society, because prior leadership role experiences benefit the development of leadership capacity (Wu, 2012) and the attainment of subsequent leadership role (McCormick et al, 2002).This new generation of Chinese female leaders will hopefully accelerate the fulfillment of gender equality in aspects of Chinese society, which have long been envisioned by the CCP regime (Croll, 1983;Stacey, 1983). …”
Section: Discussionmentioning
confidence: 84%
“…No matter which of the two explanations holds more truth, the result of this study indicates that in the near future, Chinese females may very likely rise to assume a substantial portion of leadership roles in Chinese society, because prior leadership role experiences benefit the development of leadership capacity (Wu, 2012) and the attainment of subsequent leadership role (McCormick et al, 2002).This new generation of Chinese female leaders will hopefully accelerate the fulfillment of gender equality in aspects of Chinese society, which have long been envisioned by the CCP regime (Croll, 1983;Stacey, 1983). …”
Section: Discussionmentioning
confidence: 84%
“…The findings of this study indicate that most faculty members hold a fairly high opinion of their students' leadership capacity, which supports research conducted by Duong and Le (2018) that found technical students in Ho Chi Minh City, Vietnam reported their level of leadership capacity to be high. However, Wu (2011) discovered that…”
Section: Discussionmentioning
confidence: 99%
“…demographics (Dugan, 2006;Kezar & Moriarty, 2000;Pascarella & Terenzini, 2005;Wu, 2011), college environment (Pascarella & Terenzini, 2005;Smart et al, 2002), positional leadership roles (Dugan, 2006;Kezar & Moriarty, 2000), interactions with and mentoring by faculty members (Komives, Longerbeam, Owen, Mainella, & Osteen, 2006;Thompson, 2006), community service (Dugan, 2006;Kezar & Moriarty, 2000;Thompson, 2006), participation in leadership programs (Cress, Astin, Zimmerman-Oster, & Burkhardt, 2001;Dugan, 2006;Kezar & Moriarty, 2000), and interracial relationships (Antonio, 2001). However, few have examined the connection with psychology, curricular engagement, and cocurricular involvement.…”
mentioning
confidence: 99%
“…O envolvimento do estudante com as experiências acadêmicas é uma variável importante, altamente associada com o desempenho (Loes, Pascarella, & Umbach, 2012), com a satisfação com a experiência acadêmica (Webber, Krylow, & Zang, 2013), com a permanência (Shappie & Debb, 2017), com o desenvolvimento intelectual (Chi et al, 2017) e com habilidades de liderança (Wu, 2011). Por sua vez, é importante que se conheçam as características das experiências com as quais o estudante se envolve, visto que os impactos anteriormente descritos dependem da natureza das experiências vivenciadas.…”
unclassified
“…O envolvimento do estudante varia de acordo com as características das instituições, como também, do background e de atributos pessoais do aluno, entre outras variáveis que formam uma rede complexa de influências que devem ser levadas em consideração nos estudos que tenham como interesse o envolvimento dos estudantes (Kuh & Vésper, 1997;Porto & Gonçalves, 2017). Wu (2011), em pesquisa com estudantes de Taiwan sobre o impacto das distintas experiências presentes no ensino superior na capacidade de liderança, não encontrou diferenças de gênero no que diz respeito ao envolvimento dos estudantes. Todavia, Ro & Knight (2016) encontram que homens e mulheres que cursam engenharia têm preferências distintas pelas experiências consideradas curriculares e que o impacto das mesmas também é diferente no que diz respeito aos interesses, autoeficácia e aprendizagem.…”
unclassified